Research progress on cuproptosis in cancer - Feng, Qingbo; Huo, Chenyu; Wang, Maijian; Huang, Handong; Zheng, Xingbin; Xie, Ming (Frontiers in Pharmacology, 2024)
Cuproptosis is a recently discovered form of cell death that is mediated by copper(Cu) and is a non-apoptotic form of cell death related to oligomerization of lipoylated proteins and loss of Fe-S protein clusters. Since its discovery, cuproptosis has been extensively studied by researchers for its mechanism and potential applications in the treatment of cancer. Therefore, this article reviews the specific mechanism of cuproptosis currently studied, as well as its principles and strategies for use in anti-cancer treatment, with the aim of providing a reference for cuproptosis-based cancer therapy.